The Role of Condensation Corrosion in Thermal Speleogenesis. Study of a Hypogenic Sulfidic cCve in Aix-les-Bains, France - Audra, Philippe; Hoblea, Fabien; Bigot, Jean-Yves; Nobecort, Jean-Claude (Acta Carsologica, 2007)
<span style="color: black; line-height: 115%; font-family: "Times New Roman","serif"; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Condensation-corrosion is an active speleogenetical process in thermal caves where high thermal gradient drives air convection. Wall retreat rates are greater than in meteoric caves. Conversely, evaporation produces depositional processes by replacement of limestone by gypsum and by aerosol decantation leading to the formation of popcorns. The Chevalley Aven belongs to Aix-les-Bains thermal-sulfidic cave system. Condensation occurs at the contact of cool walls of large spheres; conversely, evaporation occurs at the output of the narrow passages where the air sinks down from the upper sphere. A weathered layer and biofilms are present where slow condensation occurs. Corrosion distribution varies according to thermal rock conductivity and causes the sphere to develop upwards, laterally, and divergent. This morphodynamic pattern favors the development of stacked spheres, isolated by narrow necks, and arranged in a bush-like pattern. This development is clearly active in the vadose zone above the thermal water table. We propose that some avens above water table hypogenic caves, like Villa Luz (Mexico), may be of condensation-corrosion origin instead of phreatic. Future development will collect physical and chemical data to calculate the condensation-corrosion budget and assess its role in cave development